2021
DOI: 10.3390/s21134602
|View full text |Cite
|
Sign up to set email alerts
|

Stream-Based Visually Lossless Data Compression Applying Variable Bit-Length ADPCM Encoding

Abstract: Video applications have become one of the major services in the engineering field, which are implemented by server–client systems connected via the Internet, broadcasting services for mobile devices such as smartphones and surveillance cameras for security. Recently, the majority of video encoding mechanisms to reduce the data rate are mainly lossy compression methods such as the MPEG format. However, when we consider special needs for high-speed communication such as display applications and object detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This method can effectively improve the PSNR of the image without affecting the compression rate. Therefore, the improved formula based on the research in [ 22 ] is shown in Equation (6): …”
Section: The Proposed Lossy Image Compression Algorithmmentioning
confidence: 99%
“…This method can effectively improve the PSNR of the image without affecting the compression rate. Therefore, the improved formula based on the research in [ 22 ] is shown in Equation (6): …”
Section: The Proposed Lossy Image Compression Algorithmmentioning
confidence: 99%
“…In [ 10 ], detection relative ratios capture scene features and patterns, resulting in an extremely high dynamic range. In [ 11 ], the video transmission system with autonomously controlled throughput is proposed. The work in [ 12 ] utilized current compensation technique for X-Y channels in an LED backlight system with I-V characteristics.…”
Section: Introductionmentioning
confidence: 99%